Digital Marketing Strategy In Increasing Brand Awareness In The Industrial Era 4.0 - Yosanda Zata Aman; Dyah Setyawati; Diah Widiawati; Shallya Yudha Tama (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
In the current digital era, marketing strategies are experiencing significant changes. Rapidly developing information and communication technology has changed the way companies market products and interact with consumers. Digital marketing is one of the main tools used to increase brand awareness. This research aims to identify effective digital marketing strategies in increasing brand awareness in the digital era. This research applies qualitative research methods. The data collection technique used is literature study. The data that has been collected is then analyzed through three stages, namely data reduction, data presentation, and drawing conclusions. The research results show that marketing strategies that can be used to increase brand awareness in the industrial era 4.0 include Search Engine Optimization (SEO), content marketing, social media, influencer marketing, and data analysis. Factors that influence the effectiveness of digital marketing strategies in increasing brand awareness include content quality, consistency and targeting. Keywords : Digital Marketing, Brand Awareness, Industrial Era 4.0